Characterization of Groundwater Quality and Human Health Risk Assessment - Thanh Giao Nguyen; Nhien Thi Hong Huynh (Salehan Institute of Higher Education, 2023)
The study aimed to appraise groundwater quality in the Mekong Delta using a groundwater quality index (GWQI) and estimate human health risks associated with groundwater consumption. Groundwater samples were collected at sixty wells distributed in An Giang, Kien Giang, Hau Giang and Dong Thap provinces. Twelve water quality parameters were measured, including pH, total dissolved solids (TDS), hardness, coliform, nitrate (NO3ˉ), nitrite (NO2ˉ), ammonium (NH4+), sulfate (SO42-), iron (Fe), manganese (Mn), arsenic (As) and cadmium (Cd). The results were compared with the national regulation on groundwater quality. The findings of this study indicated that groundwater in the Mekong Delta was contaminated with microorganisms and some heavy metals (Fe, Mn, and As). This was related to anthropogenic activities, such as improperly treated domestic wastewater and agricultural and industrial wastes. Based on the results of GWQI, 30% of the total groundwater samples in the Mekong Delta were classified as very good for drinking purposes. However, over 26% of all samples were unsuitable for drinking. In terms of risk assessment, children were rather susceptible to cancer risks and adverse health effects through drinking As-contaminated groundwater than adults. The cancer risks of consuming As-contaminated groundwater for children and adults were up to 4.28×10-3that is higher than the acceptable risk. The highest aggregate hazard quotient of heavy metal-contaminated groundwater for children and adults was 9.54, which means that they could suffer adverse health effects. Groundwater is an indispensable source of freshwater in the Mekong Delta; thus, home water treatments are recommended to protect public health, and an in-depth groundwater quality and health risk assessment should be conducted. Doi: 10.28991/CEJ-2023-09-03-09 Full Text: PDF